Empowerment of the Elderly Through Balance Exercise and Creative Industry Training Using an Occupational Therapy Approach in Solok Regency - Sonya Nelson; Arif Fadli Muchlis; Fahmil Haris; Septri (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
An elderly person is defined as someone over the age of 60 who experiences physiological changes and a decline in bodily functions due to aging. The partner for this community service initiative is the Kandung community (*Kenagarian*) in Koto X District, Solok Regency. The issues faced by the partner include: (1) limited knowledge regarding individual potential, independence, and health, alongside a lack of active engagement among the elderly; and (2) employment challenges specifically for those considered